A method, device and system for detecting carbon sequestration efficiency of a steel slag calcium-based component and free total calcium
Patent Information
- Application Number
- CN202610822120.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-09
AI Technical Summary
[0003]为此,本申请提供了一种钢渣钙基组分和游离总钙固碳效率的检测方法、装置及系统,通过精准矫正本底碳干扰、建立游离总钙专属检测核算体系,解决现有检测方法结果偏差的问题
Smart Images

Figure CN122361498B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of material testing or analysis technology by measuring the properties of materials, specifically relating to the determination of carbon fixation efficiency by measuring the properties of steel slag components before and after carbon fixation, and particularly a method, apparatus and system for detecting the carbon fixation efficiency of steel slag calcium-based components and free total calcium. Background Technology
[0002] Utilizing steel slag to fix carbon dioxide is a crucial technological pathway for the resource recovery of industrial solid waste. Whether for basic laboratory research or future industrial application, a reliable method for detecting carbon fixation efficiency is essential. Currently, existing methods for detecting steel slag carbon fixation efficiency mostly rely on total carbon fixation or overall mass gain as the basis for calculation, focusing on the simple calculation of "carbon fixation rate" without establishing a dedicated system for detecting and calculating the carbon fixation efficiency of the inherent calcium-based components and free total calcium in steel slag. Furthermore, existing methods do not effectively correct for the background carbon content of steel slag, leading to systematic biases in the calculation results and further affecting the judgment of the carbon fixation efficiency of calcium-based components and free total calcium. Therefore, there is an urgent need to develop a steel slag carbon fixation efficiency detection method with high accuracy, wide applicability, and standardized calculation methods to achieve precise quantification and scientific characterization of the carbon fixation reaction, providing key support for the industrial application and standardized promotion of steel slag carbon fixation technology. Summary of the Invention
[0003] To address this, this application provides a method, apparatus, and system for detecting the calcium-based components and carbon fixation efficiency of steel slag. By accurately correcting background carbon interference and establishing a dedicated detection and accounting system for free total calcium, the method solves the problem of result deviation in existing detection methods.
[0004] The first aspect of this application provides a method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, comprising: Obtaining the test samples: Take the carbonized steel slag after carbonization treatment and the original steel slag of the same batch, and prepare them into carbonized steel slag powder samples and original steel slag powder samples that meet the preset conditions respectively. Determination of calcium-based compound content parameters: The mass fraction of calcium-based compounds in the original steel slag powder sample was determined; the calcium-based compound content is the content of calcium-based compounds calculated as calcium oxide (CaO), including but not limited to free calcium oxide, dicalcium silicate, tricalcium silicate, etc. Determination of carbon dioxide release parameters: The carbon dioxide mass fraction released by the decomposition of calcium carbonate in the carbonized steel slag powder sample and the original steel slag powder sample was obtained by performing programmed temperature rise test under an inert atmosphere. Determination of free total calcium content parameters: The free total calcium content of carbide steel slag powder samples and original steel slag powder samples were detected respectively; the free total calcium content is the content of free calcium oxide and calcium hydroxide calculated as calcium oxide (CaO); Calculation of carbon fixation efficiency: Based on the calcium-based compound content parameters, carbon dioxide precipitation parameters and free total calcium content parameters, the carbon fixation efficiency of the calcium-based components and the carbon fixation efficiency of the free total calcium in the steel slag were calculated respectively.
[0005] Optionally, the carbon fixation efficiency of the calcium-based component of the steel slag is calculated using the following formula: in: —Carbon fixation efficiency of calcium-based components in steel slag; ω C2 —After heating the steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω C1 —After heating the original steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω CaO —Mass fraction of calcium-based compounds in the original steel slag powder sample; 56—Relative molecular mass of CaO; 44 — Relative molecular mass of CO2.
[0006] Optionally, the free total calcium carbon fixation efficiency is calculated using the following formula: in: —Total free calcium carbon fixation efficiency; ω f2 —The total free calcium content of the carbide steel slag powder sample; ω f1 —The total free calcium content of the original steel slag powder sample.
[0007] Optionally, steel slag after direct carbonization treatment is tested using the formula for carbon fixation efficiency of calcium-based components and / or the formula for carbon fixation efficiency of free total calcium; steel slag after indirect carbonization treatment is tested using the formula for carbon fixation efficiency of free total calcium.
[0008] Optionally, if the calculated carbon fixation efficiency of the calcium-based components of the steel slag or the carbon fixation efficiency of the free total calcium is less than 0, it is determined that no effective carbonization reaction has occurred.
[0009] Optionally, obtaining the sample to be tested involves taking carbonized steel slag after carbonization treatment and the original steel slag from the same batch, and preparing carbonized steel slag powder samples and original steel slag powder samples that meet preset conditions, respectively. This includes taking carbonized steel slag after carbonization treatment and the original steel slag from the same batch, using a crusher to coarsely crush the steel slag to be prepared to a first particle size, then finely crushing it to a second particle size; using a ball mill to perform three-stage crushing to a third particle size; and grinding it using a sample preparation machine until a preset sample preparation time is reached to obtain carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size.
[0010] Optionally, the mass fraction of the calcium-based compound is determined using an X-ray fluorescence spectrometer. The detection conditions are as follows: sample preparation is performed using a pellet method, the excitation source is an Rh target, the tube voltage is 25–50 kV, the tube current is 40–80 mA, and the detection time is 30–120 s.
[0011] Optionally, the determination of carbon dioxide release parameters includes: performing programmed temperature rise tests on carbide steel slag powder samples and original steel slag powder samples under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder samples and original steel slag powder samples; including... The programmed temperature rise test was performed using a microcomputer differential thermal balance. The inert atmosphere preparation gas included N2 or Ar, with a gas flow rate of 10–30 mL / min and a constant heating rate of 10–20 °C / min. The starting temperature was room temperature, and the ending temperature was 800–900 °C. The temperature range in which calcium carbonate decomposed to release carbon dioxide was 500–800 °C. The decomposition start and end points were determined by analyzing the peak value of the first derivative of the thermogravimetric curve. The mass loss rate in the decomposition interval was calculated using the tangent method for baseline correction.
[0012] The determination of the total free calcium content was performed using an ethylene glycol-EDTA titration method. The reagents used included ethylene glycol, EDTA standard solution, and calcium indicator. The EDTA standard solution was a complexing titrant prepared from disodium ethylenediaminetetraacetate with a concentration of 0.01–0.02 mol / L. The calcium indicator was used to indicate the titration endpoint and was prepared by grinding calcium carboxylic acid and potassium nitrate in a mass ratio of 1:40–60.
[0013] Optionally, the ethylene glycol-EDTA titration method includes free total calcium leaching and free total calcium titration. The free total calcium leaching process is carried out in a water bath shaker at a temperature of 70–90°C, a shaking speed of 300–600 r / min, and a leaching time of 15–30 min. After leaching, the suspension is transferred to a centrifuge tube and centrifuged at 3000–5000 r / min for 5–20 min. The supernatant is then used for titration. The titration endpoint is determined by the solution turning bright blue and not fading within 30 seconds. When determining the total free calcium content, the detection range of total free calcium is 0.01% to 20% as CaO. If the total free calcium content in the sample is <0.5%, the sample weight should be increased to 1 to 2 g to ensure that the volume of EDTA standard solution consumed in the titration is not less than 5 mL.
[0014] A second aspect of this application provides a device for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, comprising, Sample acquisition module: used to acquire carbonized steel slag powder samples and raw steel slag powder samples that meet preset conditions; Calcium-based compound content parameter acquisition module: used to obtain the mass fraction of calcium-based compounds in the original steel slag powder sample; Carbon dioxide release parameter acquisition module: used to acquire the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder sample and the original steel slag powder sample. Free total calcium content parameter acquisition module: used to obtain the free total calcium content of carbide steel slag powder samples and original steel slag powder samples; Carbon fixation efficiency calculation module: used to calculate the carbon fixation efficiency of calcium-based components and the carbon fixation efficiency of free total calcium in steel slag based on the calcium-based compound content parameters, carbon dioxide precipitation parameters, and free total calcium content parameters, respectively.
[0015] A third aspect of this application provides a detection system for the calcium-based components and free total calcium carbon fixation efficiency of steel slag, comprising a sample preparation unit, a chemical composition analysis unit, a thermogravimetric analysis unit, and a calculation unit. The sample preparation unit includes a jaw crusher, a ball mill, a sample preparation machine, and a matching standard sieve. The crusher is used to coarsely crush the carbonized steel slag after carbonization treatment and its original steel slag from the same batch to the first particle size, and then finely crush it to the second particle size. The ball mill is used to further crush it to the third particle size. The sample preparation machine is used to grind the slag until the preset sample preparation time is reached to obtain carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size. The standard sieve is used to verify whether the particle size of the steel slag in each stage meets the particle size requirements. The chemical composition analysis unit includes an X-ray fluorescence spectrometer and a free total calcium detection component. The X-ray fluorescence spectrometer is used to determine the mass fraction of calcium-based compounds in the steel slag sample before carbonization. The free total calcium detection component includes a water bath shaker, a centrifuge, and a titration device, used to determine the free total calcium content of the original steel slag powder sample and the free total calcium content of the carbonized steel slag powder sample. Thermogravimetric analysis unit, including a microcomputer differential thermal balance, is used to perform programmed temperature rise tests on carbide steel slag powder samples and original steel slag powder samples under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder samples and original steel slag powder samples. The calculation unit, including data processing and controller, is used to receive detection data obtained from the chemical composition analysis unit and the thermogravimetric analysis unit, calculate the carbon fixation efficiency of calcium-based components and the carbon fixation efficiency of free total calcium in steel slag, and output the calculation results.
[0016] This application provides a method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag. The method involves obtaining the samples to be tested: taking carbonized steel slag after carbonization treatment and original steel slag from the same batch, and preparing carbonized steel slag powder samples and original steel slag powder samples respectively, both meeting preset conditions; determining the calcium-based compound content parameter: detecting the mass fraction of calcium-based compounds in the original steel slag powder sample; determining the carbon dioxide release parameter: performing a programmed temperature rise test on the carbonized steel slag powder sample and the original steel slag powder sample under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbonized steel slag powder sample and the original steel slag powder sample; and determining the free total calcium content parameter. The free total calcium content of carbonized steel slag powder samples and original steel slag powder samples were detected separately. The carbon fixation efficiency was calculated: based on the parameters of calcium-based compound content, carbon dioxide emission, and free total calcium content, the carbon fixation efficiency of the calcium-based components and the free total calcium in the steel slag were calculated respectively. This accurately corrected background carbon interference and established a dedicated carbon fixation efficiency detection and calculation system for the inherent calcium-based components and free total calcium in steel slag. This system enables a quantitative evaluation of the degree of carbonization reaction in steel slag and is applicable to the detection of carbon fixation efficiency of steel slag after different carbonization processes (direct or indirect carbonization). It provides a reliable detection method for process optimization and effect evaluation of steel slag carbonization solidification technology. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of this application. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0018] Figure 1 This is a schematic flowchart illustrating a method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, as shown in an embodiment of this application.
[0019] Figure 2 This is a schematic diagram illustrating the crushing, grinding, and screening operation steps in the embodiments of this application.
[0020] Figure 3 This is a schematic diagram of the detection device shown in the embodiments of this application.
[0021] Figure 4 This is a schematic diagram of the detection system shown in the embodiments of this application.
[0022] Figure 5 This is a schematic diagram of the structure of an electronic device shown in an embodiment of this application. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] Among related technologies, the technology of fixing carbon dioxide using steel slag is one of the important technical paths to achieve the goal of industrial solid waste resource utilization. The calcium-based components (such as free calcium oxide, dicalcium silicate, tricalcium silicate, etc.) in steel slag are the main active substances in the carbonization reaction. Among them, free calcium oxide and calcium hydroxide (collectively referred to as total free calcium) have the highest activity, and their degree of carbonization directly affects the stability and resource utilization value of steel slag.
[0025] Currently, existing methods for detecting the carbon fixation efficiency of steel slag suffer from the following technical shortcomings: First, background carbon interference is not effectively corrected. During the stockpiling process, steel slag naturally absorbs carbon dioxide from the air to form carbonates. This "background carbon" cannot be distinguished from the carbon introduced during carbonization. Existing methods directly characterize the carbon fixation amount using the total amount of carbonates in the carbonized sample, leading to systematic biases in the calculation results. Second, the evaluation dimensions are limited. Existing methods often use total carbon fixation or overall mass gain as the basis for calculation, outputting only a general "carbon fixation rate" index. This fails to distinguish between the overall carbon fixation capacity of calcium-based components and the carbon fixation efficiency of the key component, free total calcium, making it difficult to accurately guide the optimization of steel slag carbonization processes.
[0026] Therefore, this application provides a method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, see [link to relevant documentation]. Figure 1 ,include: S1. Obtain the sample to be tested: Take the carbonized steel slag after carbonization treatment and the original steel slag of the same batch, and prepare them into carbonized steel slag powder sample and original steel slag powder sample that meet the preset conditions respectively. S2. Determination of calcium-based compound content parameters: Detect the mass fraction of calcium-based compounds in the original steel slag powder sample; the calcium-based compound content is the content of calcium-based compounds calculated as calcium oxide (CaO), including but not limited to free calcium oxide, dicalcium silicate, tricalcium silicate, etc. S3. Determination of carbon dioxide release parameters: Under an inert atmosphere, the carbonized steel slag powder sample and the original steel slag powder sample were subjected to programmed temperature rise test to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbonized steel slag powder sample and the original steel slag powder sample. S4. Determination of free total calcium content parameters: The free total calcium content of carbide steel slag powder sample and original steel slag powder sample were determined respectively; the free total calcium content is the free calcium oxide and calcium hydroxide content calculated as calcium oxide (CaO); S5. Calculate carbon fixation efficiency: Based on the calcium-based compound content parameters, carbon dioxide precipitation parameters, and free total calcium content parameters, calculate the carbon fixation efficiency of the calcium-based components and the carbon fixation efficiency of the free total calcium in the steel slag, respectively.
[0027] In one embodiment provided in this application, the carbon fixation efficiency of the calcium-based component of the steel slag is calculated using the following formula: in: —Carbon fixation efficiency of calcium-based components in steel slag; ω C2 —After heating the steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω C1 —After heating the original steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω CaO —Mass fraction of calcium-based compounds in the original steel slag powder sample; 56—Relative molecular mass of CaO; 44 — Relative molecular mass of CO2.
[0028] This application incorporates the difference in carbon dioxide release before and after carbonization into the calculation of carbon fixation efficiency. After deducting the carbonized portion, the total amount of calcium-based components remaining that can participate in the new carbonization reaction. This eliminates the interference from the original carbonate background of steel slag, thereby solving the problem of uncorrected background carbon; at the same time, it introduces... The mass of newly added CO2 is corrected from "based on mass after carbonization" to "based on mass before carbonization", so as to achieve accurate quantification of the net increase in carbonization.
[0029] The denominator of the formula for the carbon fixation efficiency of calcium-based components In essence, it refers to the total amount of calcium-based components in the steel slag before carbonization that can participate in the carbonization reaction (net calcium content after deducting the already carbonized portion, expressed as CaO), molecule It is the equivalent of calcium oxide corresponding to the carbon dioxide actually combined in the carbonization reaction, and the ratio of the two is the actual carbonization conversion rate of the calcium-based component.
[0030] In one embodiment provided in this application, the free total calcium carbon fixation efficiency is calculated using the following formula: in: —Total free calcium carbon fixation efficiency; ωf2 —The total free calcium content of the carbide steel slag powder sample; ω f1 —The total free calcium content of the original steel slag powder sample.
[0031] In the formula for total free calcium carbon fixation efficiency, and The method comprehensively corrects for differences in quality benchmarks before and after carbonization and interference from the original carbonate background, reflecting the remaining proportion of free total calcium. Subtracting this ratio from 1 gives the proportion of free total calcium that was carbonized.
[0032] In one embodiment provided in this application, the steel slag after direct carbonization treatment is tested using the steel slag calcium-based component carbon fixation efficiency formula and / or the free total calcium carbon fixation efficiency formula; the steel slag after indirect carbonization treatment is tested using the free total calcium carbon fixation efficiency formula. That is, the carbon fixation efficiency of the steel slag calcium-based component in the method of this application (… The calculation applies to steel slag after direct carbonization treatment, and the free total calcium carbon fixation efficiency ( The calculation is applicable not only to steel slag after direct carbonization but also to steel slag after indirect carbonization.
[0033] This application's embodiments construct two independent carbon fixation efficiency calculation systems: one based on the carbon fixation efficiency of steel slag calcium-based components. To obtain the overall carbon fixation capacity of all carburized active calcium components in steel slag; by measuring the carbon fixation efficiency of total free calcium. This approach focuses on the free calcium component, which has the highest activity and the greatest impact on stability, ultimately achieving a multi-dimensional evaluation of the carbonization effect of steel slag.
[0034] In this application embodiment, the two core processes for carbon fixation of steel slag are defined as follows: direct carbonization treatment refers to the process in which solid steel slag directly undergoes a mineralization reaction with gas containing carbon dioxide; indirect carbonization treatment refers to the process in which steel slag is first pretreated by water leaching or acid leaching to dissolve the calcium-based components in the steel slag in the solution, and then gas containing carbon dioxide is introduced into the solution to cause the calcium-based components to undergo a mineralization reaction with carbon dioxide.
[0035] This application clarifies the applicable scope of two calculation formulas: the calcium-based component carbon fixation efficiency formula is derived based on the mass conservation law of gas-solid reactions and is applicable to direct carbonization processes; the free total calcium carbon fixation efficiency formula is derived based on the calcium element conservation law and is applicable to both direct and indirect carbonization processes, thus solving the problem of "insufficient process applicability." In one embodiment provided in this application, when the calculated result of the carbon fixation efficiency of the calcium-based component or the free total calcium carbon fixation efficiency of the steel slag is less than 0, it is determined that no effective carbonization reaction has occurred. The calculated result of the carbon fixation efficiency of the calcium-based component or the free total calcium carbon fixation efficiency of the steel slag can be accurate to 0.01%.
[0036] In one embodiment provided in this application, obtaining the sample to be tested involves taking carbonized steel slag after carbonization treatment and original steel slag from the same batch, and preparing carbonized steel slag powder samples and original steel slag powder samples that meet preset conditions, respectively. This includes taking carbonized steel slag after carbonization treatment and original steel slag from the same batch, and using a crusher to coarsely crush the steel slag to be prepared to a first particle size, then finely crush it to a second particle size; then using a ball mill to perform three-stage crushing to a third particle size; and finally using a sample preparation machine to grind it until a preset sample preparation time is reached, thereby obtaining carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size.
[0037] In one alternative implementation, see [link to specific implementation]. Figure 2 The crushing, grinding, and screening operations include: S101: Take the carbonized steel slag after carbonization treatment and the original steel slag of the same batch, and use a crusher to process the steel slag to be prepared. Then, use a jaw crusher to coarsely crush it to a particle size of no more than 19.0 mm (i.e., all of it passes through a 19 mm screen) and finely crush it to a particle size of no more than 9.5 mm (i.e., all of it passes through a 9.5 mm screen). S102: The particles are crushed in three stages by ball mill to a particle size of no more than 4.75 mm (i.e., all of them pass through a 4.75 mm sieve). S103: Grind the steel slag using a sample preparation machine until the sample preparation time reaches 2 minutes to obtain a carbonized steel slag powder sample with a particle size ≤150μm and a raw steel slag powder sample.
[0038] In one embodiment provided in this application, the parameter for determining the calcium-based compound content is: detecting the mass fraction of calcium-based compounds in the original steel slag powder sample; the calcium-based compound content is the content of calcium-based compounds calculated as calcium oxide (CaO), including but not limited to free calcium oxide, dicalcium silicate, tricalcium silicate, etc. The mass fraction of the calcium-based compound was determined using an X-ray fluorescence spectrometer. The detection conditions were as follows: sample preparation was performed using a pellet method, the excitation source was an Rh target, the tube voltage was 25–50 kV, the tube current was 40–80 mA, and the detection time was 30–120 s.
[0039] In one embodiment provided in this application, the determination of the carbon dioxide release parameter includes: performing programmed temperature rise tests on a carbide steel slag powder sample and a raw steel slag powder sample under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder sample and the raw steel slag powder sample; including... The programmed temperature rise test was performed using a microcomputer differential thermal balance. The inert atmosphere preparation gas included N2 or Ar, with a gas flow rate of 10–30 mL / min. The heating rate was constant at 10–20 °C / min, with an initial temperature of room temperature and an ending temperature of 800–900 °C. The temperature range in which calcium carbonate decomposes to release carbon dioxide was 500–800 °C. The decomposition start and end points were determined by analyzing the peak value of the first derivative of the thermogravimetric curve (i.e., the DTG curve). The mass loss rate in the decomposition interval was calculated using the tangent method for baseline correction to eliminate interference from other non-calcium carbonate decomposition processes on the measurement results.
[0040] In one embodiment provided in this application, the parameter for determining the total free calcium content is: the total free calcium content of the carbide steel slag powder sample and the original steel slag powder sample are detected respectively; the total free calcium content is the content of free calcium oxide and calcium hydroxide calculated as calcium oxide (CaO).
[0041] The determination of the total free calcium content was performed using an ethylene glycol-EDTA titration method. The reagents used included ethylene glycol, EDTA standard solution, and calcium indicator. The EDTA standard solution was a complexing titrant prepared from disodium ethylenediaminetetraacetate with a concentration of 0.01–0.02 mol / L. The calcium indicator was used to indicate the titration endpoint and was prepared by grinding calcium carboxylic acid and potassium nitrate in a mass ratio of 1:40–60.
[0042] The ethylene glycol-EDTA titration method includes free total calcium leaching and free total calcium titration. The free total calcium leaching process is carried out in a water bath shaker at a temperature of 70–90°C, a shaking speed of 300–600 r / min, and a leaching time of 15–30 min. After leaching, the suspension is transferred to a centrifuge tube and centrifuged at 3000–5000 r / min for 5–20 min. The supernatant is then used for titration determination. The titration endpoint is determined by the solution turning bright blue and not fading within 30 seconds. When determining the free total calcium content, the detection range for free total calcium is 0.01% to 20% (calculated as CaO). If the free total calcium content in the sample is <0.5%, the sample weight should be increased to 1-2 g to ensure that the volume of EDTA standard solution consumed in the titration is not less than 5 mL. This application introduces the difference in carbon dioxide precipitation before and after carbonization into the calculation of carbon fixation efficiency. After deducting the carbonized portion, the remaining total amount of calcium-based components that can participate in the new carbonization reaction is eliminated, thus eliminating the background interference of the original carbonate in the steel slag. At the same time, the mass of newly added CO2 is corrected from "based on the mass after carbonization" to "based on the mass before carbonization," achieving effective correction of the background carbon in the steel slag and significantly improving the accuracy of carbon fixation efficiency detection.
[0043] This application establishes two independent methods for calculating carbon fixation efficiency: one for calcium-based components and one for free total calcium. The former reflects the overall carbon fixation capacity of all active calcium components in steel slag, while the latter focuses on the free calcium component with the highest activity and the greatest impact on stability. This achieves a multi-dimensional and accurate evaluation of the carbonization effect of steel slag, providing a more comprehensive technical basis for the resource utilization of steel slag. This application clarifies that the formula for calculating the carbon fixation efficiency of calcium-based components is applicable to direct carbonization processes, while the formula for calculating the carbon fixation efficiency of free total calcium is applicable to both direct and indirect carbonization processes. Whether using the direct carbonization method based on gas-solid reactions or the indirect carbonization method based on gas-liquid-solid multiphase reactions, the methods in this application can be used to evaluate carbon fixation efficiency, covering the main process routes of existing steel slag carbonization technologies and possessing broad applicability.
[0044] Example Steel slag from a steel plant's converter was selected. Raw steel slag from the same batch and carbonized steel slag after direct carbonization treatment (75% CO2 concentration, 600℃, carbonization for 10 min) were taken, crushed, ground, and sieved to obtain samples with a particle size ≤150 μm. The mass fraction ω of calcium-based compounds in the steel slag before carbonization was determined using X-ray fluorescence spectrometry. CaO =50.92%; The total free calcium content ω in the steel slag before and after carbonization was determined by ethylene glycol-EDTA titration. f1 =2.39%, ω f2 =0.52%; The amount of carbon dioxide released from the steel slag before and after carbonization was determined by a microcomputer differential thermal balance. C1 =7.76%, ω C2 =9.52%. Substituting the above data into the formula for carbon sequestration efficiency of calcium-based steel slag, the following calculation was performed: Carbon fixation efficiency of calcium-based components: Free total calcium carbon fixation efficiency: In the above embodiments, if the background carbon correction is ignored and the carbon fixation amount is characterized only by the carbon dioxide release after carbonization (9.52%), the roughly estimated carbon fixation efficiency is approximately 4.86%, which is significantly lower than the 6.03% calculated by the method of this application. This difference stems from the fact that this application introduces the carbon dioxide release before carbonization (7.76%) to subtract the original carbonate background of the steel slag, effectively avoiding the interference of background carbon on the detection results.
[0045] In the above embodiments, the overall carbon fixation efficiency of the calcium-based component (6.03%) differed by orders of magnitude from the carbon fixation efficiency of free total calcium (77.82%). This result indicates that under the carbonization process conditions, most of the free calcium component has been carbonized, but the dominant calcium-based mineral phase in the steel slag has not yet fully reacted. Relying solely on a single carbon fixation rate index will fail to identify this crucial information, potentially leading to misjudgments in the direction of process optimization. Therefore, a multi-dimensional evaluation is necessary.
[0046] This application also provides a device for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, see [link to relevant documentation]. Figure 3 The detection device 3 includes, Sample acquisition module 301: used to acquire carbonized steel slag powder samples and original steel slag powder samples that meet preset conditions; Calcium-based compound content parameter acquisition module 302: used to obtain the mass fraction of calcium-based compounds in the original steel slag powder sample; Carbon dioxide release parameter acquisition module 303: used to acquire the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in carbonized steel slag powder samples and original steel slag powder samples. Free total calcium content parameter acquisition module 304: used to acquire the free total calcium content of carbide steel slag powder sample and original steel slag powder sample; Carbon fixation efficiency calculation module 305: used to calculate the carbon fixation efficiency of calcium-based components and the carbon fixation efficiency of free total calcium in steel slag based on the calcium-based compound content parameters, carbon dioxide precipitation parameters and free total calcium content parameters, respectively.
[0047] This application also provides a detection system for the calcium-based components and free total calcium carbon fixation efficiency of steel slag, see [link to relevant documentation]. Figure 4 The detection system 4 includes a sample preparation unit 401, a chemical composition analysis unit 402, a thermogravimetric analysis unit 403, and a calculation unit 404. These units work collaboratively and are sequentially connected. Their specific structure and functions are as follows: The sample preparation unit 401 includes a jaw crusher, a ball mill, a sample preparation machine, and a matching standard sieve. The crusher is used to coarsely crush the carbonized steel slag after carbonization treatment and its original steel slag from the same batch to the first particle size, and then finely crush it to the second particle size. The ball mill is used to further crush it to the third particle size. The sample preparation machine is used to grind the slag until the preset sample preparation time is reached to obtain carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size. The standard sieve is used to verify whether the particle size of the steel slag in each stage meets the particle size requirements. After graded crushing, grinding, and sieving, a uniform steel slag sample with a particle size ≤150μm that meets the requirements for subsequent testing is finally obtained. The chemical composition analysis unit 402 includes an X-ray fluorescence spectrometer and a free total calcium detection component. The X-ray fluorescence spectrometer is used to determine the mass fraction of calcium-based compounds in the steel slag sample before carbonization. The free total calcium detection component includes a water bath shaker, a centrifuge, and a titration device, used to determine the free total calcium content in the original steel slag powder sample and the free total calcium content in the carbonized steel slag powder sample. Thermogravimetric analysis unit 403 includes a microcomputer differential thermal balance, which is used to perform programmed temperature rise tests on carbide steel slag powder samples and original steel slag powder samples under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder samples and original steel slag powder samples. The calculation unit 404 includes a data processing and controller, which receives the detection data obtained by the chemical composition analysis unit and the thermogravimetric analysis unit, calculates the carbon fixation efficiency of the calcium-based components and the carbon fixation efficiency of the free total calcium in the steel slag, and outputs the calculation results.
[0048] Figure 5 This is a schematic diagram of the structure of the electronic device 5 shown in the embodiments of this application.
[0049] See Figure 5 Electronic device 5 includes memory 501 and processor 502.
[0050] Electronic device 5 includes memory 501 and processor 502; The memory 501 is connected to the processor 502 and is used to store programs; Processor 502 is used to implement some or all of the methods described above by running programs stored in memory 501.
[0051] Specifically, the aforementioned electronic device 5 may further include: a bus, a communication interface 503, an input device 504, and an output device 505.
[0052] The processor 502, memory 501, communication interface 503, input device 504, and output device 505 are interconnected via a bus. Among them: A bus can include a pathway for transmitting information between various components of a computer system.
[0053] Processor 502 can be a Central Processing Unit (CPU), or other general-purpose processors, digital signal processors (DSPs), application-specific integrated circuits (ASICs), field-programmable gate arrays (FPGAs), or other programmable logic devices, discrete gate or transistor logic devices, discrete hardware components, etc. A general-purpose processor can be a microprocessor or any conventional processor.
[0054] Processor 502 may include a main processor, as well as a baseband chip, modem, etc.
[0055] Memory 501 may include various types of storage units, such as system memory, read-only memory (ROM), and permanent storage devices. ROM may store static data or instructions required by processor 502 or other modules of the computer. Permanent storage devices may be read-write storage devices. Permanent storage devices may be non-volatile storage devices that retain stored instructions and data even when the computer is powered off. In some embodiments, permanent storage devices use mass storage devices (e.g., magnetic or optical disks, flash memory) as permanent storage devices. In other embodiments, permanent storage devices may be removable storage devices (e.g., floppy disks, optical drives). System memory may be a read-write storage device or a volatile read-write storage device, such as dynamic random access memory. System memory may store some or all of the instructions and data required by the processor during operation. Furthermore, memory 501 may include any combination of computer-readable storage media, including various types of semiconductor memory chips (e.g., DRAM, SRAM, SDRAM, flash memory, programmable read-only memory), and disks and / or optical disks may also be used. In some implementations, memory 501 may include a removable storage device that is readable and / or writable, such as a laser disc (CD), a read-only digital multifunction optical disc (e.g., DVD-ROM, dual-layer DVD-ROM), a read-only Blu-ray disc, an ultra-high density optical disc, a flash memory card (e.g., SD card, mini SD card, Micro-SD card, etc.), a magnetic floppy disk, etc. Computer-readable storage media do not contain carrier waves or transient electronic signals transmitted wirelessly or via wired connections.
[0056] Input device 504 may include a device for receiving data and information input by the user, such as a keyboard, mouse, camera, scanner, light pen, voice input device, touch screen, pedometer, or gravity sensor.
[0057] Output device 505 may include devices that allow information to be output to a user, such as a display screen, printer, speaker, etc.
[0058] The communication interface 503 may include a device that uses any transceiver to communicate with other devices or communication networks, such as Ethernet, Radio Access Network (RAN), Wireless Local Area Network (WLAN), etc.
[0059] The processor 502 executes the program stored in the memory 501 and calls other devices, which can be used to implement some or all of the methods described above.
[0060] Furthermore, the method according to this application can also be implemented as a computer program product, which includes computer program code instructions for performing some or all of the steps in the method described above. Optionally, the computer program can be stored on a readable storage medium of a computer device or in the cloud; the processor of the computer device reads the computer program from the readable storage medium or the cloud.
[0061] Computer program products can be written in any combination of one or more programming languages to perform the operations of the embodiments of this application. The programming languages include object-oriented programming languages such as Java and C++, as well as conventional procedural programming languages such as C or similar languages. The program code can be executed entirely on the user's computing device, partially on the user's computing device, as a standalone software package, partially on the user's computing device and partially on a remote computing device, or entirely on a remote computing device or server.
[0062] The aforementioned computer program product can be implemented through hardware, software, or a combination thereof. In one optional embodiment, the computer program product is specifically embodied in a computer storage medium; in another optional embodiment, the computer program product is specifically embodied in a software product, such as a software development kit (SDK), etc.
[0063] Alternatively, this application may be implemented as a computer-readable storage medium (or a non-transitory machine-readable storage medium or a machine-readable storage medium) storing executable code (or computer program or computer instruction code) that, when executed by a processor of an electronic device (or server, etc.), causes the processor to perform part or all of the steps of the methods described above according to this application.
[0064] The computer-readable storage medium may be any combination of one or more readable media. A readable medium may be a readable signal medium or a readable storage medium. A readable storage medium may, for example, include, but is not limited to, electrical, magnetic, optical, electromagnetic, infrared, or semiconductor systems, apparatuses, or devices, or any combination thereof. More specific examples of readable storage media (a non-exhaustive list) include: electrical connections having one or more wires, portable disks, hard disks, random access memory (RAM), read-only memory (ROM), erasable programmable read-only memory (EPROM or flash memory), optical fibers, portable compact disk read-only memory (CD-ROM), optical storage devices, magnetic storage devices, or any suitable combination thereof.
[0065] The various embodiments of this application have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, characterized in that, include: Obtaining the test samples: Take the carbonized steel slag after carbonization treatment and the original steel slag of the same batch, and prepare them into carbonized steel slag powder samples and original steel slag powder samples that meet the preset conditions respectively. Determination of calcium-based compound content parameters: The mass fraction of calcium-based compounds in the original steel slag powder sample was determined; Determination of carbon dioxide release parameters: Under an inert atmosphere, programmed temperature rise tests were performed on both carbide steel slag powder samples and raw steel slag powder samples to obtain the mass fraction of carbon dioxide released from the decomposition of calcium carbonate in the samples. The programmed temperature rise test started at room temperature and ended at 800–900℃. The temperature range for carbon dioxide release from calcium carbonate was 500–800℃. The decomposition start and end points were determined by analyzing the peak value of the first derivative of the thermogravimetric curve. The mass loss rate within the decomposition range was calculated using the tangent method for baseline correction to eliminate interference from non-calcium carbonate decomposition processes on the measurement results. Determination of free total calcium content parameters: The free total calcium content of carbide steel slag powder samples and original steel slag powder samples were determined respectively; the free total calcium content is the content of free calcium oxide and calcium hydroxide calculated as calcium oxide (CaO); Calculation of carbon fixation efficiency: Based on the parameters of calcium-based compound content, carbon dioxide release, and free total calcium content, the carbon fixation efficiency of the calcium-based components and the carbon fixation efficiency of the free total calcium in the steel slag are calculated respectively. This includes introducing the difference in carbon dioxide release before and after carbonization, calculating the total amount of effective calcium-based components that can participate in the carbonization reaction after deducting the background calcium carbonate components of the steel slag, and eliminating the interference of the original carbonate background in the steel slag; and correcting the mass of newly added carbon dioxide from the mass after carbonization to the mass before carbonization. The carbon fixation efficiency of the calcium-based component in the steel slag is calculated using the following formula: in: —Carbon fixation efficiency of calcium-based components in steel slag; ω C2 —After heating the steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω C1 —After heating the original steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω CaO —Mass fraction of calcium-based compounds in the original steel slag powder sample; 56—Relative molecular mass of CaO; 44 — Relative molecular mass of CO2; The free total calcium carbon fixation efficiency is calculated using the following formula: in: —Total free calcium carbon fixation efficiency; ω f2 —The total free calcium content of the carbide steel slag powder sample; ω f1 —The total free calcium content of the original steel slag powder sample.
2. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, Steel slag after direct carbonization treatment was tested using the formula for carbon fixation efficiency of calcium-based components and / or the formula for carbon fixation efficiency of free total calcium; steel slag after indirect carbonization treatment was tested using the formula for carbon fixation efficiency of free total calcium.
3. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, When the calculated carbon fixation efficiency of the calcium-based components of the steel slag or the carbon fixation efficiency of the free total calcium is less than 0, it is determined that no effective carbonization reaction has occurred.
4. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, The process of obtaining the test samples involves taking carbonized steel slag after carbonization treatment and original steel slag from the same batch, and preparing them into carbonized steel slag powder samples and original steel slag powder samples that meet the preset conditions, respectively. The process includes taking carbonized steel slag after carbonization treatment and the original steel slag from the same batch, using a crusher to coarsely crush the steel slag to be prepared to the first particle size, then finely crushing it to the second particle size; then using a ball mill to perform three-stage crushing to the third particle size; and finally grinding it using a sample preparation machine until the preset sample preparation time is reached, to obtain carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size.
5. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, The mass fraction of the calcium-based compound was determined by X-ray fluorescence spectrometry. The detection conditions were as follows: sample preparation was performed by pellet compression, the excitation source was an Rh target, the tube voltage was 25–50 kV, the tube current was 40–80 mA, and the detection time was 30–120 s.
6. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, The parameters for determining the amount of carbon dioxide released are as follows: under an inert atmosphere, a programmed temperature rise test is performed on the carbonized steel slag powder sample and the original steel slag powder sample to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbonized steel slag powder sample and the original steel slag powder sample. include, The programmed temperature rise test was performed using a microcomputer differential thermal balance. The inert atmosphere preparation gas included N2 or Ar, with a gas flow rate of 10–30 ml / min and a constant heating rate of 10–20 °C / min.
7. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 1, characterized in that, The determination of the total free calcium content was performed using an ethylene glycol-EDTA titration method. The reagents used in the ethylene glycol-EDTA titration method included ethylene glycol, EDTA standard solution, and calcium indicator. The EDTA standard solution was a complexing titrant prepared from disodium ethylenediaminetetraacetate with a concentration of 0.01–0.02 mol / L. The calcium indicator was used to indicate the titration endpoint and was prepared by mixing and grinding calcium carboxylic acid and potassium nitrate at a mass ratio of 1:40–60.
8. The method for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag as described in claim 7, characterized in that, The ethylene glycol-EDTA titration method includes free total calcium leaching and free total calcium titration. The free total calcium leaching process is carried out in a water bath shaker at a temperature of 70–90°C, a shaking speed of 300–600 r / min, and a leaching time of 15–30 min. After leaching, the suspension is transferred to a centrifuge tube and centrifuged at 3000–5000 r / min for 5–20 min. The supernatant is then used for titration determination. The titration endpoint is determined by the solution turning bright blue and not fading within 30 seconds. When determining the total free calcium content, the detection range of total free calcium is 0.01% to 20% as CaO. If the total free calcium content in the sample is <0.5%, the sample weight should be increased to 1 to 2 g to ensure that the volume of EDTA standard solution consumed in the titration is not less than 5 mL.
9. A device for detecting the calcium-based components and free total calcium carbon fixation efficiency of steel slag, characterized in that, include, Sample acquisition module: used to acquire carbonized steel slag powder samples and raw steel slag powder samples that meet preset conditions; Calcium-based compound content parameter acquisition module: used to obtain the mass fraction of calcium-based compounds in the original steel slag powder sample; The carbon dioxide release parameter acquisition module is used to acquire the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder sample and the original steel slag powder sample. Specifically, the carbide steel slag powder sample and the original steel slag powder sample are subjected to a programmed temperature rise test under an inert atmosphere. The programmed temperature rise test starts at room temperature and ends at 800–900℃. The temperature range for the calcium carbonate to release carbon dioxide is 500–800℃. The decomposition start and end points are determined by analyzing the peak value of the first derivative of the thermogravimetric curve. The mass loss rate in the decomposition range is calculated using the tangent method for baseline correction to eliminate interference from non-calcium carbonate decomposition processes on the measurement results. Free total calcium content parameter acquisition module: used to obtain the free total calcium content of carbide steel slag powder samples and original steel slag powder samples; Carbon fixation efficiency calculation module: used to calculate the carbon fixation efficiency of calcium-based components and the carbon fixation efficiency of free total calcium in steel slag based on the calcium-based compound content parameters, carbon dioxide release parameters, and free total calcium content parameters, respectively; it includes introducing the difference in carbon dioxide release before and after carbonization, calculating the total amount of effective calcium-based components that can participate in the carbonization reaction after deducting the background calcium carbonate components of the steel slag, eliminating the interference of the original carbonate background of the steel slag; and correcting the mass of newly added carbon dioxide from the mass after carbonization to the mass before carbonization; The carbon fixation efficiency of the calcium-based component in the steel slag is calculated using the following formula: in: —Carbon fixation efficiency of calcium-based components in steel slag; ω C2 —After heating the steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω C1 —After heating the original steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω CaO —Mass fraction of calcium-based compounds in the original steel slag powder sample; 56—Relative molecular mass of CaO; 44 — Relative molecular mass of CO2; The free total calcium carbon fixation efficiency is calculated using the following formula: in: —Total free calcium carbon fixation efficiency; ω f2 —The total free calcium content of the carbide steel slag powder sample; ω f1 —The total free calcium content of the original steel slag powder sample.
10. A detection system for the calcium-based components and free total calcium carbon fixation efficiency of steel slag, characterized in that, It includes a sample preparation unit, a chemical composition analysis unit, a thermogravimetric analysis unit, and a calculation unit. The sample preparation unit includes a jaw crusher, a ball mill, a sample preparation machine, and a matching standard sieve. The crusher is used to coarsely crush the carbonized steel slag after carbonization treatment and the original steel slag of the same batch to the first particle size, and then finely crush it to the second particle size. The ball mill is used to continue the tertiary crushing to the third particle size. The sample preparation machine is used to grind the slag until the preset sample preparation time is reached to obtain carbonized steel slag powder samples and original steel slag powder samples that meet the target particle size. Standard sieves are used to verify whether the particle size of the steel slag in each stage meets the requirements. The chemical composition analysis unit includes an X-ray fluorescence spectrometer and a free total calcium detection component. The X-ray fluorescence spectrometer is used to determine the mass fraction of calcium-based compounds in the steel slag sample before carbonization. The free total calcium detection component includes a water bath shaker, a centrifuge, and a titration device, used to determine the free total calcium content of the original steel slag powder sample and the free total calcium content of the carbonized steel slag powder sample. The thermogravimetric analysis unit includes a microcomputer differential thermal balance, used to perform programmed temperature rise tests on carbide steel slag powder samples and original steel slag powder samples under an inert atmosphere to obtain the mass fraction of carbon dioxide released by the decomposition of calcium carbonate in the carbide steel slag powder samples and original steel slag powder samples; wherein, the programmed temperature rise test starts at room temperature and ends at 800-900℃; the temperature range for calcium carbonate to release carbon dioxide is 500-800℃; the decomposition start point and end point are determined by analyzing the peak value of the first derivative of the thermogravimetric curve; the mass loss rate in the decomposition range is calculated using the tangent method for baseline correction to eliminate the interference of non-calcium carbonate decomposition processes on the measurement results; The calculation unit, including a data processing and controller, receives detection data from the chemical composition analysis unit and the thermogravimetric analysis unit, calculates the carbon fixation efficiency of the calcium-based components and the carbon fixation efficiency of the free total calcium in the steel slag, and outputs the calculation results. This includes incorporating the difference in carbon dioxide release before and after carbonization, calculating the total effective calcium-based components that can participate in the carbonization reaction after deducting the background calcium carbonate components of the steel slag, eliminating the interference from the original carbonate background of the steel slag, and correcting the mass of newly added carbon dioxide from being based on the mass after carbonization to being based on the mass before carbonization. The carbon fixation efficiency of the calcium-based component in the steel slag is calculated using the following formula: in: —Carbon fixation efficiency of calcium-based components in steel slag; ω C2 —After heating the steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω C1 —After heating the original steel slag powder sample, the calcium carbonate decomposed and the carbon dioxide mass fraction was obtained. ω CaO —Mass fraction of calcium-based compounds in the original steel slag powder sample; 56—Relative molecular mass of CaO; 44 — Relative molecular mass of CO2; The free total calcium carbon fixation efficiency is calculated using the following formula: in: —Total free calcium carbon fixation efficiency; ω f2 —The total free calcium content of the carbide steel slag powder sample; ω f1 —The total free calcium content of the original steel slag powder sample.